Anodic Oxidation of Phenol by Mixed-Metal Oxide Electrodes: Identification of Transformation By-Products and Toxicity Assessment. Issue 7 (4th May 2017) - Barışçı, Sibel; Turkay, Ozge; Öztürk, Hazal; Şeker, Mine Gül
Abstract : This study examined the oxidation of phenol by electrochemical processes using different mixed-metal oxide (MMO) anodes, namely, Ti/Pt, Ti/IrO2 -Ta2 O5, Ti/Ta2 O5 -SnO2 -IrO2, Ti/RuO2 and Ti/IrO2 -RuO2 . First, the effectiveness of different anodes by phenol oxidation was evaluated with the help of such parameters as cyclic voltammetry (CV), current efficiencies and degradation rates. The Ti/Pt anode was found to be the most effective of all types of anodes, as almost complete phenol degradation was gained with its use. Then, optimum operational conditions, applied current density and initial pH, were determined using Ti/Pt as the anode. By-products of phenol degradation (benzoquinone, hydroquinone, pyrocatechol, oxalic and maleic acid) arising gradually during the reaction were determined via high-performance liquid chromatography (HPLC) for all selected anodes. There was a considerable difference between the anodes with regard to degradation efficiency and concentrations of formed by-products. The toxicity was evaluated by measuring the natural luminescence of the bacteria, Vibrio fischeri, for all selected anodes. According to the toxicity assessment, a number of toxic by-products were formed from phenol degradation for all selected anodes. However, their toxicity decreased at the end of electrolysis on the Ti/Pt anode.